(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
Let Ɍ be a commutative ring with identity and Ң be left unitary Ɍ-module. This study deals the concept of almost approximaitly nearly semiprime submodules as new generalization of semiprime submodules, also generalizations of (prime, nearly prime, approximaitly prime and approximaitly semiprime) submodules. We give same basic properties, and characterizations of this concept. Furthermore, we explain the relationships between almost approximaitly nearly semiprime submodules with (semiprime, prime, nearly semiprime, nearly prime, approximaitly semiprime, and approximaitly prime) submodules.